2020
DOI: 10.1101/2020.05.15.098442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MEKK3-MEK5-ERK5 Signaling Promotes Mitochondrial Degradation

Abstract: Mitochondria are vital organelles that coordinate cellular energy homeostasis and have important roles in cell death. Therefore, the removal of damaged or excessive mitochondria is critical for maintaining proper cellular function. The PINK1-Parkin pathway removes acutely damaged mitochondria through a well-characterized mitophagy pathway, but basal mitochondrial turnover occurs via distinct and less well-understood mechanisms. Here we report that the MEKK3-MEK5-ERK5 kinase cascade is required for mitochondria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…It is noteworthy that the list of genes from the AD core modules with supporting genetic evidence (Table 1) includes a gene of the MAPK pathway, MAP3K3. This gene encodes MEKK3, a kinase acting upstream of ERK5 described as a positive regulator of mitophagy 71 . Interestingly, the dysfunction of the www.nature.com/scientificreports/ autophagy-lysosomal system and in particular the mitophagy impairment has been observed in AD patients and AD animal models 72 , and the dysregulation of the MAPK signaling pathway could be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the list of genes from the AD core modules with supporting genetic evidence (Table 1) includes a gene of the MAPK pathway, MAP3K3. This gene encodes MEKK3, a kinase acting upstream of ERK5 described as a positive regulator of mitophagy 71 . Interestingly, the dysfunction of the www.nature.com/scientificreports/ autophagy-lysosomal system and in particular the mitophagy impairment has been observed in AD patients and AD animal models 72 , and the dysregulation of the MAPK signaling pathway could be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…MAP3K3 is the key kinase of the MAPK signaling pathway and plays a crucial role in cell proliferation, apoptosis, and inflammatory and immune responses [58]. Previous studies showed that MAP3K3 plays a role in promoting cell survival, and MAP3K3 could promote mitochondrial degradation through the MAP3K3/MEK5/ERK5 pathway, thus increasing the content of mitochondria [59], while overexpression of Map3k3 offers resistance to apoptosis via activating the nuclear factor κB signal pathway [60]. More recently, Yuan et al determined that the Map3k2/3 deficiency led to increased total ROS from neutrophils upon stimulation by fMLP, MIP2, or PMA, indicating the importance of kinase activity in the regulation of ROS release [61].…”
Section: Discussionmentioning
confidence: 99%